Learning Revit 2011 - Polding, Jay (InfiniteSkills, 2010)
"In this Revit Architecture 2011 training video, instructor Jay Polding walks you through the intricacies of this masterful BIM program. AutoDesk Revit is a popular choice for creating BIM models and 3D renderings of buildings and rooms, and the 2011 version of this software adds many new and exciting features. Using our highly popular method of computer based learning, Jay Polding starts with the basics of the user interface and installation, but quickly moves into creating a project that you will use to apply what Jay is instructing you on. You will learn to create walls, columns, windows, doors, how to apply 3D views, elevations, how to create skylights, and how to render, print and export your CAD files. Jay makes it easy and fun to learn, making your retention of the material much higher! By the completion of this software training tutorial, you will be fully capable of creating and sharing your projects using Revit 2011. Extensive working files are included to allow you to work alongside the author and immediately apply what you are learning."--Resource description page.